CFD Commercial Software and Air Conditioning & Refrigeration - 谷现良; 赵加宁; 高军; 高甫生 (Zhileng xuebao)
This paper introduces the general structure and characteristic of CFD commercial software. For the research and design work of air conditioning and refrigeration, the commonly used CFD commercial software is described with regard to the suitability, the grid characteristic, the numerical algorithm, the difference scheme, and the turbulence model. On the whole, each of the software has its own merit and suitability. The software must be analyzed and selected in application on the basis of the practical problem which is studied.